Exploring the Relationship between Islamic Financial Development, Energy Consumption, and Environmental Quality - Abduh, Muhamad; Buys, Witrie Annisa; Aziz, Sumayyah Abdul (International Journal of Energy Economics and Policy, 2022)
The relationship between financial development, energy consumption and the environment has been a popular topic in the last three decades. However, a minimal number of studies have been done within the Islamic finance framework despite its fifty years of establishment. This study aims to fill that gap by exploring the impact of Islamic financial development on energy consumption and environmental quality. Total financing and financial access are the two variables to represent Islamic financial advancement while millions tonnes of oil equivalent and CO2 emission as the proxy for energy consumption and environmental quality respectively. Focusing on six world top Islamic finance countries from 2013 to 2018, the findings show that Islamic financial development contributes significantly to the increase in energy consumption and the degradation of environmental quality.